Kajian Pemilihan Jenis Bahan Perancah Beton Pada Pembangunan Gedung Bertingkat - Suparno Suparno (Politeknik Negeri Semarang, 2012)
Construction and its concrete scaffolding is a temporary construction (construction support in concrete construction), due to the cost required is quite large, approximately 1/3 of the total cost of the concrete construction, it is based on the analysis of unit price work (SNI 03-7394-2008), therefore it needs to be examined in order to reduce the cost of its construction and for the cost efficiency in the construction of storey buildings. This research conducted assessments of the selection of scaffold materials for the manufacture of concrete construction, the objective is to select the best type of scaffold material thus it would be able to reduce the cost of the buildings construction. By using the method of Analytic Hierarchy Process (AHP), the assessment was conducted on the three alternative types of scaffold materials of concrete, these materials were the bamboo, the wood, and the iron / pipe galvasnis (scaffolding). The result of the calculation by the alternative assesment, is that the higher rank is the scaffolding which is 0,531, while the bamboois in the second with the total score 0,301 and the wood is the lowest with the total score 0,168. It can be assumed that the result of this research on the basis of five criteria, namely: the cost; the strenght and the durability;the effectiveness of the instalation and dismantling; the security and the safety work, as well as its impact on the invironment that the scaffolding is the best alternative chioce of the materials.